An exploratory study investigating children's perceptions of dental behavioural management techniques - Davies, E. Bethan; Buchanan, Heather (Wiley, 2013)
Background: Behaviour management techniques (BMTs) are utilised by dentists to aid children's dental anxiety (DA). Children's perceptions of these have been underexplored, and their feedback could help inform paediatric dentistry.